Analisis Kesesuian Gambar Dan Penggunaan Kata Dan Tanda Baca Pada Media Spanduk Berbasis Digital - Abdul Sakti; B. Syukroni Baso (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research aims to analyze the suitability of images and the use of words and punctuation on digital media. The research method used was observation of a digital banner displaying an image of a chair with the words